The Internet As A Business Game Changer: A Study On Invisible Consumption Spaces In Nanjing Old City - Wang, Jinyi; Sun, Shijie; Cong, Xiaoyu (AESOP, 2024)
With the recent development of online-to-offline (O20) industries in China, the Internet has become a game- changer, facilitating the creation of new forms of spaces. Taking Nanjing old city as a case study, this paper identifies invisible consumption spaces that are not situated on the streets or in shopping malls but are primarily located inside high-rise buildings and rely on online platforms to operate. The distribution of invisible consumption spaces presents characteristics of central agglomeration and multi-polar clustering. Based on decision tree algorithms, an analysis of a typical area indicates that spatial costs, property rights, and building management and support are the primary influencing factors. Additionally, commercial-residential buildings play a crucial role as carriers of spatial clustering. This paper argues that the emergence and development of invisible consumption spaces is a manifestation of the diversification of old city consumption spaces and a significant bottom-up regeneration strategy in the Internet era. Keywords: Invisible consumption space, O20, distribution characteristics, spatial clustering, space regeneration
Game changer? Planning for just and sustainable urban regions, Paris, 8-12th July 2024